A Qualitative Study of Stress in University Staff - Mark, George; Smith, Andrew (Advances in Social Sciences Research Journal, 2018)
Research has shown that university staff report high levels of stress. Most of this research has used questionnaires and the aim of the present study was to develop the area using interview data. The mixed responses given about the definition of stress reflect the definitional debates in psychology as whether “stress” is the cause of problems, or if it is the response. All of the participants claimed to either to have, or were currently experiencing stress, which illustrates how widespread stress at work can be. The wide range of stressors described shows the complexity and number of stressful situations that employees in academic employment can be faced with. Many of the consequences of stress at work described by participants related to anxiety and other symptoms of worry. Trouble sleeping was a common problem, as were issues relating to taking work worries home. There were various suggestions made about how to help avert or deal with stress in the workplace, and most of these centred around communication and better training and selection of management. Several participants believed that the university should be treated more like a business, with professional managers advised by professors. Nearly all of the participants were unsatisfied with the current method of selecting management on the basis of academic merit. The use and results of the interview methods illustrate that while questionnaire methods are typically more general and are thus applicable to a wider range of different populations, qualitative studies can give an extra dimension to results, and can provide key information about stressors and outcomes that questionnaires based on traditional stress models cannot. Indeed using interviews to guide the use of questionnaire selection, which could then be analysed in line with the structure of the Demands-Resources-Individual Effects (DRIVE) framework, could be an important direction in future research on specific populations.